Stereotactic ablative body radiotherapy in patients with oligometastatic cancers: a prospective, registry-based, single-arm, observational, evaluation study. Issue 1 (January 2021) - Chalkidou, Anastasia; Macmillan, Thomas; Grzeda, Mariusz T; Peacock, Janet; Summers, Jennifer; Eddy, Saskia; Coker, Bola; Patrick, Hannah; Powell, Helen; Berry, Lee; Webster, Gareth; Ostler, Peter; et al.
Summary: Background: Stereotactic ablative body radiotherapy (SABR) is increasingly being used to treat oligometastatic cancers, but high-level evidence to provide a basis for policy making is scarce. Additional evidence from a real-world setting is required. We present the results of a national study of patients with extracranial oligometastases undergoing SABR, representing the largest dataset, to our knowledge, on outcomes in this population so far. Methods: In 2015, National Health Service (NHS) England launched a Commissioning through Evaluation scheme that funded a prospective, registry-based, single-arm, observational, evaluation study of patients with solid cancer and extracranial oligometastases treated with SABR. Prescribed doses ranged from 24–60 Gy administered in three to eight fractions. The study was done at 17 NHS radiotherapy centres in England. Patients were eligible for the scheme if aged 18 years or older with confirmed primary carcinoma (excluding haematological malignancies), one to three extracranial metastatic lesions, a disease-free interval from primary tumour development to metastases of longer than 6 months (with the exception of synchronous colorectal liver metastases), a WHO performance status of 2 or lower, and a life expectancy of at least 6 months. The primary outcome was overall survival at 1 year and 2 years from the start of SABR treatment. The study is now completed. Findings: Between June 15, 2015, and Jan 30, 2019, 1422 patients were recruited from 17 hospitals in England. The median age of the patients was 69 years (IQR 62–76), and the most common primary tumour was prostate cancer (406 [28·6%] patients). Median follow-up was 13 months (IQR 6–23). Overall survival was 92·3% (95% CI 90·5–93·9) at 1 year and 79·2% (76·0–82·1) at 2 years. The most common grade 3 adverse event was fatigue (28 [2·0%] of 1422 patients) and the most common serious (grade 4) event was increased liver enzymes (nine [0·6%]). Notreatment-related deaths were reported. Interpretation: In patients with extracranial oligometastatic cancer, use of SABR was associated with high overall survival and low toxicity. 'The study findings complement existing evidence from a randomised, phase 2 trial, and represent high-level, real-world evidence supporting the use of SABR in this patient cohort, with a phase 3 randomised, controlled trial to confirm these findings underway. Based on the selection criteria in this study, SABR was commissioned by NHS England in March, 2020, as a treatment option for patients with oligometastatic disease. Funding: NHS England Commissioning through Evaluation scheme.